Analisis Pemodelan Hidrologi Dan Hidraulika Sistem Drainase Menggunakan SWMM: Studi Kasus: Kecamatan Cisurupan, Garut - Sulwan Permana; Fajar Abdul Aziz (Jurnal Konstruksi, 2026)
This study evaluates the performance of the drainage system in Cisurupan Subdistrict, Garut Regency, which often experiences flooding due to limited channel capacity. The main objective is to assess the effectiveness of the existing drainage system and formulate improvement alternatives through modeling using the Storm Water Management Model (SWMM) version 5.2. The study uses a descriptive-quantitative approach based on case studies with 10 years of rainfall data, topography, and channel conditions. Hydrological analysis produced a 5-10 year return period rainfall and a maximum intensity of 23.96 mm/hour. SWMM simulation results showed that some channel segments were only able to accommodate 85% of their full capacity, with potential overflow in the JN2–JN3 segment and a peak discharge of 0.21 m³/s. These conditions indicate that the channel capacity is inadequate for high rainfall intensity. Therefore, it is recommended to increase the channel dimensions and construct retention ponds to reduce the risk of flooding. The development of a drainage system, especially in areas that are prone to flooding during rainfall, requires attention, particularly the maintenance of the drainage network.